PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN RUTE DOMESTIK GARUDA INDONESIA DI KOTA AMBON - Saleky, Saul Ronald Jacob (Jurnal Minds: Manajemen Ide dan Inspirasi, 2017)
This study aims to analyze the effect of service quality on customer satisfaction of Garuda Indonesia flight service on domestic route in Ambon City. Data are collected using questionnaires distributed to 135 customers who use Garuda Indonesia flight to and from Ambon. The data collected was further processed and calculated using SPSS 21 and then analyzed using regression analysis. The result shows that service quality’s factors have positive and significant influence to Garuda Indonesia customer satisfaction on domestic flight route to and from Ambon. Furthermore, the results of this study recommend that in an effort to improve customer satisfaction, the management of Garuda Indonesia can continue to improve quality services continuously in the future.